Factors Related to Maternal COVID-19 Vaccination Status in Mpunda Public Health Center - Warnaini, Cut; Rahma, Jaini (Jurnal Biologi Tropis, 2024)
Pregnant women were among the vulnerable population for COVID-19 infection. Therefore, it is important for pregnant women to carry out a complete COVID-19 vaccination. Complete COVID-19 vaccination status for pregnant women is when the pregnant woman has received two doses of the vaccine, where the first dose of vaccination begins in the second trimester of pregnancy and the second dose is given according to the interval of the type of vaccine. Even though the Covid-19 vaccination program has contributed to reducing death rates and infectious diseases, there will still be concerns and doubts among pregnant women and women of reproductive age. Therefore, this research is aimed to observe and analyze factors related to Maternal COVID-19 Vaccination Status specifically in Mpunda Public Health Center, Bima. This study employs a mixed-method analysis and was conducted in Mpunda Public Health Center involving 136 pregnant women. We found that socioeconomic factor such as income level, prior vaccination status, and vaccination history was significantly associated with COVID-19 vaccination status among pregnant women, but not history of adverse events. We also concluded that fear of vaccine was significantly associated with COVID-19 vaccination status among pregnant women. Results of this research hopefully can add to the growing body of evidence regarding maternal COVID-19 vaccination status and aid the policy-making process regarding this topic.